TESTIMONY AND LIMITS OF THE REPRESENTATION IN DAUGHTERS OF KAVILLACA. ORAL TRADITION OF THE WOMEN OF HUAROCHIRÍ - Viera, Sara (2011)
This article intends to address the problem of the testimony in the textDaughters of Kavillaca. Oral Tradition of the Women of Huarochirí. Besides,it questions the power of representation that the researchers bestow onthe informants. To pass a text from orality to writing always involves anact of manipulation and appropriation by part of the researcher. It is alsoa negotiation which reveals the struggles and tensions as a result of twodifferent cultures in contact. The text in question does not escape from theunderlying dynamics of the testimony. Therefore, we will do a review on thetensions that occurred during the process of compilation of testimonies andthe levels of representation granted to the informants. We believe that inspite of the good intentions of the researchers by providing a greater degree ofrepresentation this is buried when they assume all the editing process withoutthe participation of the informants.